Academic pluralism - Gutiérrez Gómez, Edgar (2019)
Universities worldwide became a community of academics and teachers, as the stages of their historical process passed, they were accommodated to the circumstances of the historical context. The origin of universitas "totality" derived from the universum, "gathered in a whole", gradually made an academic turn to pluralism, discarding elitism to give greater access to the public that the universities of their interest are looking for. The University Reform of Córdoba fed back academic pluralism in Latin America, as indicated: “A mixed university was born among us, with science institutes and professional schools, the latter also endowed with research centers” (Chuaqui, 2002, pp. 563- 565) is thus, currently universities have the mission of implementing their research institutes with quality scientific products and a multidisciplinary component. To this scientific consideration, we publish our second issue of the journal PURIQ respecting the academic pluralism of its authors, who complied by presenting their articles of interest.